STRATEGI MARKETING PADA UMKM SNACK BU IYAM - Dini Sulastri; Kartini Delawati; Dwi Epty Hidayaty (PT Naureen Digital Education, 2023)
The marketing strategy is one of the most important things in entrepreneurial activities, both small-scale businesses and large-scale businesses. In the current era, there are many MSME businesses that can increase people's income. One type of service business that has increased rapidly is the business in the food sector. The food business is certainly in great demand by many customers so that from this business they can earn and can recruit other people to work with them. This research was conducted in a snack business at Griya Panorama Indah No.F3/46, Purwasari, Kec. Purwasari, Karawang, West Java 41373. Snack Mrs. Iyam, whose address is at Griya Panorama Indah No.F3/46, Purwasari, Kec. Purwasari, Karawang, West Java 41373. The purpose of this study is to describe the food business process, identify strengths, weaknesses, opportunities and threats for Mrs. Iyam's snacks. Formulating alternative strategies for developing this food business. Select priority strategies that can be used in developing Mrs. Iyam's snack business. The method used in this research is to identify Mrs. Iyam's snack business processes using descriptive analysis.